2018
DOI: 10.3389/fpubh.2018.00160
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Psychological Impairment in Rural Adolescent Girls: Pilot Data From “KOKAN” Region of Western India

Abstract: Background: Adolescence is a period during which psychological foundations are laid down as well as consolidated. Not much information is available on rural Indian adolescent girls and their psychological health.Methods: We did a pilot survey of psychological health of 80 adolescent girls residing at KOKAN region of western India. Psychological health was evaluated using Youth Paediatric Symptom Checklist (Y-PSC) consisting of 35 items with maximum score of 70. Girls with a score >30 were classified as psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
(23 reference statements)
6
8
1
4
Order By: Relevance
“…The urban and metropolitan subjects had similar intake of cereals, milk and milk products (Figure 3D) (17). There are similar reports documented by other workers of low dietary calcium intake in adolescent (17) and post-menopausal women (1820). Interestingly, a study of migrant workers in metropolitan cities had higher dietary calcium intake much above the RDA (21, 22).…”
Section: Nutrition Trends—india (1975–2017)supporting
confidence: 91%
“…The urban and metropolitan subjects had similar intake of cereals, milk and milk products (Figure 3D) (17). There are similar reports documented by other workers of low dietary calcium intake in adolescent (17) and post-menopausal women (1820). Interestingly, a study of migrant workers in metropolitan cities had higher dietary calcium intake much above the RDA (21, 22).…”
Section: Nutrition Trends—india (1975–2017)supporting
confidence: 91%
“…In India, the issue of malnutrition has received considerable critical attention as studies show that 23% adult females are undernourished and 22% are obese,[10] and studies determine that more than 50% adolescent girls are underweight in our country. [11] This observation is also supported by other studies showing that the prevalence of undernutrition in 10–24 years is ranging from 56.4 to 68.5%. [12] Inadequate nutrition along with adverse life style behaviors has accentuated the problem of chronic diseases in the young adults.…”
Section: Introductionsupporting
confidence: 80%
“…India has been on the forefront of DOHaD research, and though all the research points toward nutritional deficiencies at various stages of life cycle, actual findings of various studies vary considerably. 25 Given these variations and the findings of our cross-sectional studies [26][27][28] over the last two decades, we concluded that further systematic research is needed. Therefore, we have designed a prospective cohort study of adolescent girls of the Ratnagiri district.…”
Section: Open Accessmentioning
confidence: 88%
“…27 A small cross-sectional study on 80 adolescent girls showed association between micronutrient deficiencies and psychological impairment. 28…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%